Outcomes of treatment for relapsed acute lymphoblastic leukaemia in children with Down syndrome - Meyr, Franziska; Escherich, Gabriele; Mann, Georg; Klingebiel, Thomas; Kulozik, Andreas; Rossig, Claudia; Schrappe, Martin; Henze, Günter; Stackelberg, Arend von; Hitzler, Johann (British journal of haematology, 2013)
Children with Down syndrome (DS) have a greater risk for developing both acute lymphoblastic leukaemia (ALL) and significant adverse effects of chemotherapy. We investigated their outcome with, and tolerance of, treatment protocols for relapsed ALL optimized in the paediatric population without DS. Probability of survival and causes of treatment failure were determined for 49 children with DS and a matched cohort of 98 children without DS among 2160 children treated for relapsed ALL in clinical trials conducted by the Berlin-Frankfurt-Münster ALL Relapse Study Group between 1983 and 2012. Despite more favourable ALL relapse characteristics, children with DS experienced lower event-free (EFS) and overall survival (OS) than the control group without DS (EFS 17 ± 08% vs. non-DS 41 ± 06%, P = 0·006; OS 17 ± 09% vs. non-DS 51 ± 06%, P < 0·001). Children with DS developed more frequently fatal complications of treatment (34 ± 07% vs. non-DS 10 ± 04%, P < 0·001). During the last decade, EFS and OS were no longer significantly different in children with and without DS (EFS 31 ± 09% vs. 36 ± 09%, P = 0·399; OS 31 ± 12% vs. 53 ± 09%, P = 0·151). DS proved an independent prognostic factor of outcome after ALL relapse. Induction deaths and treatment-related mortality but not subsequent relapse were the main barrier to successful outcomes of relapse therapy in children with DS.